Prevalence of Polypharmacy, Hyperpolypharmacy and Potentially Inappropriate Medication Use in Older Adults in India: A Systematic Review and Meta-Analysis - Bhagavathula, Akshaya S.; Vidyasagar, Kota; Chhabra, Manik; Rashid, Muhammed; Sharma, Rishabh; Bandari, Deepak K.; Fialova, Daniela (Frontiers in Pharmacology, 2021)
Background: Older people often receive multiple medications for chronic conditions, which often result in polypharmacy (concomitant use of 5‒9 medicines) and hyperpolypharmacy (concomitant use of ≥10 medicines). A limited number of studies have been performed to evaluate the prevalence of polypharmacy, hyperpolypharmacy, and potentially inappropriate medication (PIM) use in older people of developing countries. The present study aimed to investigate regional variations in the prevalence of polypharmacy, hyperpolypharmacy, and PIM use in older people (60+ years) in India. Methods: Studies were identified using Medline/PubMed, Scopus, and Google Scholar databases published from inception (2002) to September 31, 2020. Out of the total 1890 articles, 27 were included in the study. Results: Overall, the pooled prevalence of polypharmacy was 49% (95% confidence interval: 42 – 56; p<0.01), hyperpolypharmacy was 31% (21 – 40; p<0.01), and PIM use was 28% (24 – 32; p<0.01) among older Indian adults. Polypharmacy was more prevalent in North-east India (65%, 50 – 79), whereas hyperpolypharmacy was prevalent in south India (33%, 17 – 48). Region-wise estimates for the pooled prevalence of PIM use in India were as follows: 23% (21 – 25) in East, 33% in West (24 – 42), 17.8% in North (11 – 23), and 32% (26 – 38) in South India. The prevalence of PIM use in adults aged ≥70 years was 35% (28 – 42), in those taking more medications (≥5.5/day) was 27% (22 – 31), and in adults using a high number of PIMs (≥3) was 29% (22 – 36). Subgroup analysis showed that cross-sectional studies had a higher pooled prevalence of polypharmacy 55% (44 – 65) than cohorts 45% (37 – 54). Hyperpolypharmacy in inpatient care settings was 37% (26 – 47), whereas PIM use was higher in private hospitals 31% (24 – 38) than government hospitals 25% (19 – 31). Conclusion: Polypharmacy and hyperpolypharmacy are widely prevalent in India. About 28% of older Indian adults are affected by PIM use. Thus, appropriate steps are needed to promote rational geriatric prescribing in India.